HUBUNGAN ANTARA NILAI KEJUJURAN DAN PRIBADI YANG OTENTIK DENGAN PERILAKU MAHASISWA UNIVERSITAS BUNDA MULIA - Yohanes Probo Dwi (Psibernetika, 2015)
Higher education in the world, we recognize the existence of some general courses that must be given to all students of various study programs. At the University of Bunda Mulia, general courses such as Religion and Ethics and Pancasila and Citizenship known subjects Human Character and Behavior. This course is given as a provision to allow students to know better who he is. Know more about the potential in him, trying to get to know the surrounding natural environment and the most important thing is how he can maintain and preserve the natural surroundings in the continuity of life. The relationship between the value of personal honesty and authentic to the student’s  behavior is research effort conducted as a follow-up of subjects Human Character and Behavior ever given. Whetever the course is to give effect to the student’s behavior. The method used is distributing questionnaires and conduct interviews of 5-8 semester students, meaning those who have taken who have taken the course of Human Character and Behavior.   Keywords: personal, honesty, authentic, students.